Heparin coating on 3D printed poly (l-lactic acid) biodegradable cardiovascular stent via mild surface modification approach for coronary artery implantation - Lee, Sang Jin; Jo, Ha Hyeon; Lim, Kyung Seob; Lim, Dohyung; Lee, Soojin; Lee, Jun Hee; Kim, Wan Doo; Jeong, Myung Ho; Lim, Joong Yeon; Kwon, Il Keun; Jung, Youngmee; Park, Jun-Kyu; et al. (ELSEVIER SCIENCE SA, 2019)
In the last decade, stent implantation therapy has been widely performed in the clinic. Although the patient's cardiovascular state depends on their age, gender, and health condition, the development of customized individual stents has been limited. Thus, a patient-specific stent manufacturing system should be devised for more successful stent therapy. In this study, we prepared a 3D printed PLA biodegradable polymeric stent using polydopamine (PDA), polyethyleneimine (PEI) and heparin (Hep) chemistry to prevent restenosis and thrombosis with anticoagulation and good blood compatibility. Physico-chemical characterization indicated that pristine PLA substrates were well modified as the amine abundant surface allowed for coating of a large amount of Hep. From in vitro and ex vivo analysis, heparinized 3D PLA stents showed excellent thromboresistance and hemocompatibility functions as well as modulation of smooth muscle cell (SMC) and endothelial cell (EC) proliferation. In an in vivo study, the heparinized 3D PLA stent showed the widest lumen area with the least neointimal hyperplasia and without atherosclerosis or thrombosis. All of these assessments clearly confirmed that our innovative strategy may suggest a useful paradigm as a preparation method for a patient-customized fully biodegradable individual stent for successful implantation therapy. This would find wide utilization for cardiovascular clinical applications.
Keywords: DRUG-ELUTING STENTS; IN-VIVO DEGRADATION; BARE METAL STENT; MECHANICAL-PROPERTIES; BIORESORBABLE SCAFFOLDS; COVALENT IMMOBILIZATION; CELL-PROLIFERATION; COATED STENT; RESTENOSIS; POLYDOPAMINE